THE STATUS OF THE INTERNATIONAL TREATIES OF HUMAN RIGHTS IN THE BRAZILIAN CONSTITUTIONAL SYSTEM - Renato, Khamis Braz Mehanna (Anales Universitatis Apulensis Series Jurisprudentia; No 16 (2013): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2013)
The objective of this paper is to present the problem of the status qualification of the international treaties of human rights into the Brazilian constitutional system, especially after the advent of the 45 amendment of the Constitution. Key words: international treaties; human rights.